Fast Model for Evaluation of the Thyroid Dosimetry During Chest Tumor Radiotherapy - Yiling Wang; Min Zheng; Ling He; Jinhui Xu; Gang Yin; Jie Zhou; Yue Zhao; Ming Jiang; Jie Wang (Dose-Response, 2019)
Due to the reported high incidence of thyroid cancer induced by radiotherapy, dose assessment is significant to prevent thyroid late effects. Thyroid dosimetry can be evaluated either by entrance skin dose (ESD) measured with thermoluminescent dosimeter (TLD) arrays or by absorbed dose (AD) computed with treatment planning system. However, their correlation has hardly been reported in any publications. Moreover, the reported measurement procedures for thyroid ESD are usually inefficient. This study aims to provide a fast model for efficient acquisition of thyroid ESD and analyze the coherent relationship between ESD and AD. We conducted the study on the China radiation anthropomorphic phantom with intentionally delineated cancers, irradiated by a Varian 23EX linac. We have measured the ESD with TLD at 5 different points, while computed AD with the Oncentra Masterplan TPS. The ESD at the middle gorge of thyroid has exhibited significant linear correlation with those measured at other points. Furthermore, a regressive model has been proposed to predict thyroid AD from ESD. Consequently, it is recommended to only measure the ESD at the middle gorge of thyroid for an efficient dose assessment. The validity of the regressive model to predict thyroid AD from ESD has also been demonstrated.